Immune surveillance and humoral immune responses in kidney transplantation – A look back at T follicular helper cells - Julien Subburayalu; Julien Subburayalu; Julien Subburayalu (Frontiers in Immunology, 2023)
T follicular helper cells comprise a specialized, heterogeneous subset of immune-competent T helper cells capable of influencing B cell responses in lymphoid tissues. In physiology, for example in response to microbial challenges or vaccination, this interaction chiefly results in the production of protecting antibodies and humoral memory. In the context of kidney transplantation, however, immune surveillance provided by T follicular helper cells can take a life of its own despite matching of human leukocyte antigens and employing the latest immunosuppressive regiments. This puts kidney transplant recipients at risk of subclinical and clinical rejection episodes with a potential risk for allograft loss. In this review, the current understanding of immune surveillance provided by T follicular helper cells is briefly described in physiological responses to contrast those pathological responses observed after kidney transplantation. Sensitization of T follicular helper cells with the subsequent emergence of detectable donor-specific human leukocyte antigen antibodies, non-human leukocyte antigen antibodies their implication for kidney transplantation and lessons learnt from other transplantation “settings” with special attention to antibody-mediated rejection will be addressed.